ð›¿âˆ’derived and ð›¿âˆ’Scattered Sets - Zainab Aodia Athbanaih (Al-Qadisiyah Journal of Pure Science, 2017)
In this paper, we introduce new class of Sets called ð›¿âˆ’Scattered and investigate the Properties of this Set. we use the concept of Î´-limit point and ð›¿âˆ’drived Set to construct the definition of this class. we give the relation between types of scattered Sets and types of limit points .